Antarctic sea ice phytoplankton growth rates and survival mechanisms - Kumadiro, Lisa (Department of Chemical Engineering, 2025)
Phytoplankton play an important role in the Southern Ocean food web being the primary producers of food, particularly in winter, and partaking in the uptake of CO2 from the atmosphere via photosynthesis. Despite being photosynthetic organisms, phytoplankton survive at the bottom of sea ice where there is very little irradiance for up to 6 months. Sea ice phytoplankton are understudied. This is mainly because in situ studies on sea ice are not only expensive but logistically difficult. Some researchers have elected to bring sea ice phytoplankton from the Southern Ocean to land-based facilities. This has seen some logistical difficulties as it meant either changing the habitat phytoplankton would have been for transportation, thus changing the species originally found in the Southern Ocean or transporting phytoplankton in ice cores and losing species due to brine drainage or osmotic stress from temperature changes in the core. The objectives of this study were to optimize a previously designed hybrid tank for the purpose of obtaining and preserving phytoplankton species from the Marginal Ice Zone of the Southern Ocean to land-based facilities. The study also included design of an environmental chamber to be used for housing phytoplankton obtained during experimentation. Responses to temperature and irradiance variation on phytoplankton from the Marginal Ice Zone of the Southern Ocean were then evaluated using the designed environmental chamber. The solid-liquid hybrid system known as the hybrid tank was successfully optimized by reducing the size of the tank, adding irradiation to the tank, and making improvements to the sampling protocol. The tank was used to obtain ice cores from the Southern Ocean to the University of Cape Town in winter 2022. Post the winter cruise one hybrid tank sample was melted, and microscopic analysis conducted on the sample. In comparison with transportation of phytoplankton in a solid core and in a liquid melt in the dark, the hybrid tank resulted in an increase in phytoplankton cell concentration. Furthermore, the optimized hybrid tank improved preservation of species transported when compared to the initial tank. A desktop environmental chamber made from Perspex and insulated with polystyrene was successfully designed. The environmental chamber offers temperature and irradiation control by making use of a cold plate attached to a chiller and an LED light. Experiments conducted on the diatom species revealed that all the sea ice species were shade adaptive being photo inhibited at irradiances beyond 42μmolm-2s-1 with the exception of Navicula spp, Cylindrotheca closterium and the unidentified pennates. The diatom species also preferred warmer environments i.e., 8°C to 5°C.